Pengaruh E-Service Quality dan Perceived Security Terhadap Minat Beli Ulang Melalui E-Satisfaction Konsumen Aplikasi E-Commerce Tokopedia - Hanifah Azzahra (Fakultas Ekonomi dan Bisnis, 2025)
This research aims to examine the influence of E-Service Quality and Perceived Security on Repurchase Intention through E-Satisfaction of Tokopedia e-commerce application consumers. The type of data in this research is quantitative. The data source used is primary data. The sampling tehnique in this research was Purposive Sampling with a total of 257 respondents tested. The data collection tehnique in this research was distributing questionnaries online. Data analysis in this research uses the Partial Least Squares-Structural Equation Model (PLS-SEM) analysis method with the SmartPLS 4.0 data processing tool. The result of this research show that: 1) E-Service Quality has a significant effect on E-Satisfaction; 2) Perceived Security has a significant effect on E-Satisfaction; 3) E-E-Satisfaction has a significant effect on Repurchase Intention; 4) E-Service Quality has a significant effect on Repurchase Intention; 5) Perceived Security has a significant effect on Repurchase Intention; 6) E-Service Quality has a significant effect on Repurchase Intention mediated by E-Satisfaction; 7) Perceived Security has a significant effect on Repurchase Intention mediated by E-Satisfaction.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: E-Service Quality; Perceived Security; Repurchase Intention; E Satisfaction